Islamic social finance and green finance to achieve SDGS through minimizing post harvesting losses in Bangladesh - Julia, Taslima; Muhammad Noor, Anwar; Kassim, Salina (IIUM Press, 2020)
The whole world is passing through an unprecedented period and struggling to overcome the economic and financial losses caused by a tiny virus COVID 19. Bangladesh is no exception. The economy of the country is agricultural-based and post-harvesting losses of fruits and vegetables is a significant issue here. This paper tries to investigate the old problem from a different perspective, with a new strategy, hoping to mitigate the impairment. Basically, renewable energy-based cold storage can solve the issue. Green financing, along with Islamic Social Financing, can play a vital role to facilitate the cold storage opportunities to the rural farmers. This paper, following a qualitative research method, is trying to offer a solution to minimize the post-harvesting losses. The implementation of this solution can help the rural mass to get rid of the poverty, hunger and malnutrition problems. In this effort not only good health and well-being will be ensured, but also partnership business practices will be enhanced while guaranteeing affordable clean energy uses. Consequently, the successful implementation of the new strategy can help the country to achieve several sustainable development goals, some directly and some indirectly.